2017
DOI: 10.1115/1.4037358
|View full text |Cite
|
Sign up to set email alerts
|

On the Source of the Systematic Error of the Pressure Measurement Film Applied to Wheel–Rail Normal Contact Measurements

Abstract: This paper presents research activities regarding the systematic error of the pressure measurement film when measuring the area of the wheel–rail contact. In particular, an explanation for the different error values shown by the different film types was sought. A finite element model was created based on the assumption that not only the film, but also the microcapsules on top of it alter the results. The performance of the existing film models was enhanced by defining microcapsules with element failure and del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Alternatively, a conventional material model can be assigned to the elements by defining a constitutive law [31], as done in this work. The finite element model employed so far to replicate the Hertzian experiments conducted in the laboratory [26,27] was accordingly adapted for the material calibration procedure as depicted in Fig. 1.…”
Section: Film Model Calibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, a conventional material model can be assigned to the elements by defining a constitutive law [31], as done in this work. The finite element model employed so far to replicate the Hertzian experiments conducted in the laboratory [26,27] was accordingly adapted for the material calibration procedure as depicted in Fig. 1.…”
Section: Film Model Calibrationmentioning
confidence: 99%
“…The finely meshed film model used in previous studies, however, was considerably simplified into a single layer of gasket elements. The thickness dimension was set to 90 lm based on experimental observations [26] and a radial dimension of 100 lm was defined for each element so as to match the measurement resolution [33]. The bottom nodes of the flat body were vertically constrained and the normal force was introduced as pressure on the spherical body.…”
Section: Film Model Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Further investigations about the systematic error of pressure measurement film can be found in numerous resources. 45,46,74 Comparison of ultrasonic testing with FEA Zhou et al 24 reported about ultrasonic measurements with a full wheel and an edited rail to place an ultrasonic scanning array. They carried out various tests with different loads and different rolling speeds (max 5 mm/s).…”
Section: Comparison Of Pressure Measurement Film With Fea And/ or Hertzmentioning
confidence: 99%
“…In the experimental research, some experimental methods were applied to measure the contact pressure distribution, such as a Tekscan pressure sensor [8] and a prescale measurement film [9,10]. However, these experimental methods must insert a thin film between the contacting bodies, which is a cause of measurement error.…”
Section: Introductionmentioning
confidence: 99%